2019
DOI: 10.33140/anfs.04.02.3
|View full text |Cite
|
Sign up to set email alerts
|

Genotype X Environment Interaction for Quality Traits in Bread Wheat Genotype Tested At Six Environments

Abstract: The study was conducted to evaluate the effect of GEI and its magnitude on the grain quality of bread wheat genotypes in Ethiopia. 15 bread wheat genotypes were evaluated using RCBD with four replications at six different locations in Ethiopia during 2017/18 cropping season. Combine Analysis of variance showed highly significant (P<0.001) differences among genotype, environment and GEI for investigated quality traits except GEI shows non-significant difference in dry gluten and gluten index. The environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
4
0
0
Order By: Relevance
“…Consistent findings with prior research studies globally, as shown by Horvat et al. (2012), Mekuria and Admassu (2011), Alemu and Gerenfes (2019), and Pasha et al. (2007), emphasize the wide range of WG contents in different bread wheat varieties.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent findings with prior research studies globally, as shown by Horvat et al. (2012), Mekuria and Admassu (2011), Alemu and Gerenfes (2019), and Pasha et al. (2007), emphasize the wide range of WG contents in different bread wheat varieties.…”
Section: Discussionsupporting
confidence: 90%
“…Location‐specific TKW values further emphasize the influence of the environment on TKW, with wide‐ranging values observed at different sites, as noted by Mekonnen and Gashaw (2019). Variations in TKW, as reported by Mekuria and Admassu (2011), showcase the impact of genotype on kernel size, ranging from 36 to 40 g. The reported effects of genotypic (G), environmental (E), and their interaction (GE) on grain weight align with previous research (Alemu & Gerenfes, 2019; Shah et al., 2009) indicating the multifaceted nature of TKW determination influenced by genetic makeup and environmental factors.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations